Detection of data from the UWB microstrip resonator type RFID tag - Hossain, Abul K M Z; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
For last few decades many proposals have been made to successfully read the RFID passive tags. Each method has its own advantages and disadvantages. There are many techniques omni-present for the researches to read the UWB passive tags. A new tecnique has been proposed to read the existing conventional UWB microstrip resonator tag. Instead of using a continuous chirp as an interrogation signal, a chirp-hold signal has been used to read the tag which is more power efficient. The method has been verified by generating a six bit chirp-hold signal. The relative amplitudes’ variation of the tuned and detuned chirp-hold frequencies depends on the information stored in the tag that the data bits from the tag has been detected.